Employee Development and Training: How HRM Helps in Staying Competitive in the Changing Market Condition - Arfan Akbar,; Dr. Sajjad Ahmad,; Muhammad Ali,; Dr Muhammad Tariq Fayyaz,; Irshad Ali,; Muhammad Asad Akram Bhatti, (Al-Qanṭara, 2024)
Background: Organizations must continuously adapt to evolving conditions in an increasingly dynamic and competitive global market to maintain their competitive edge. Human Resource Management (HRM) ensures employees have the necessary skills and knowledge to meet these challenges. Employee development and training have become pivotal strategies for organizations aiming to stay relevant and competitive. Objective: This study aims to explore the role of HRM in facilitating employee development and training, focusing on how these practices contribute to organizational competitiveness in changing market conditions. The objective is to identify key HRM practices that are most effective in fostering a skilled and adaptable workforce. Method: The research employs a convergent mixed-methods approach, integrating both quantitative surveys and qualitative semi-structured interviews. The quantitative component involves the distribution of standardized surveys to HR professionals and employees across a sample of 150 organizations from various industries, focusing on evaluating HRM-led training and development initiatives. The survey achieved a response rate of 80% (120 out of 150 organizations), providing robust data for statistical analysis. In parallel, qualitative data were collected through semi-structured interviews with 30 HR professionals (representing 20% of the organizations) and 50 employees (33% of the surveyed sample), selected through purposive sampling. The interviews aimed to explore deeper insights into the impact of training and development on organizational performance and employee adaptability. Data from both methods were analyzed using SPSS for quantitative analysis and thematic analysis for qualitative data, ensuring a comprehensive understanding of the phenomena under study. Result: The analysis of the quantitative survey data revealed that 72% of the organizations reported a significant improvement in organizational performance following the implementation of HRM-led training and development initiatives. Additionally, 68% of employees indicated enhanced adaptability to changing job roles due to these programs. The qualitative interviews supported these findings, with HR professionals and employees consistently emphasizing the positive impact of targeted training on both performance metrics and individual adaptability. The thematic analysis identified key themes: increased employee confidence, improved problem-solving skills, and greater job satisfaction. Together, these results underscore the effectiveness of HRM-led training and development initiatives in fostering organizational growth and employee resilience. Conclusion: The findings highlight the need for targeted interventions to address the barriers to effective history-taking among medical and dental students and house officers. Enhancing communication skills training, providing more structured time for history taking, and fostering a supportive educational environment are crucial steps to improve this essential clinical skill.